Lead Free Solders - Kar, Abhijit (IntechOpen, 2019)
This book provides some of the most advanced research observations and in-depth knowledge behind lead-free soldering. Readers will find a description of different cutting-edge techniques used for improving the reliability of interconnects manufacturing. Some of the most unconventional topics covered in this book include solder joint formation for microelectronic devices at room temperature and the possibility of soldering ceramic materials, which is limited due to the poor wettability of ceramic substrates with commercial solders following classical soldering techniques. We also discuss the possibilities of nanoscale preparation of solder joints for bringing down the processing temperature so that it does not affect the packaging technologies. Readers will find that precise, systematic discussion of solder joint formation and its interfacial characterization has been depicted for each technique used in different chapters. This book is of interest to both fundamental researchers and also to practicing scientists and will prove invaluable to all those working in industry and academia.